Analysis of Healthcare Workers' Knowledge About Vital Sign Zero and Identify-Isolate-Inform (3I) System in the Diagnosis and Prevention of Infectious Diseases in Chinese Tertiary Hospitals - Zhijun Zhang; Yongjie Sha; Fengshi Jing; Weiming Tang; Shixing Tang (Frontiers Media S.A., 2022)
ObjectiveTo explore the current knowledge and application of vital sign zero and the identify-isolate-inform (3I) system among healthcare workers in China in order to provide a reference for future improvement of healthcare workers' awareness of personal protection and prevention and control measures of infectious diseases.MethodsThe questionnaire was used to investigate the basic information of health care workers, their knowledge and application of Vital sign zero and the 3I system. A total of 602 forms of health care workers from tertiary hospitals were randomly collected and included for analysis.ResultsThe survey showed that 45.30% and 57.30% of the healthcare workers from Chinese tertiary hospitals know about vital sign zero and 3I system while 51.80% and 57.30% of them applied these measures in their clinical practices. Logistics regression analysis results showed that healthcare workers aged 35 years old and below were less aware of vital sign zero than those above 50 years old (OR = 0.405, 95% CI: 0.174-0.942, P = 0.036). Compared with those in Northwest China, healthcare workers who worked in East China (OR = 0.147, 95% CI: 0.031-0.702, P = 0.016), Central China (OR = 0.085, 95% CI: 0.018-0.403, P = 0.002), Southwest China (OR = 0.083, 95% CI: 0.014-0.48, P = 0.006) and North China (OR = 0.201, 95% CI: 0.042-0.966, P = 0.045) were less aware of vital sign zero while the healthcare workers in Northeast China (OR=9.714, 95% CI: 1.091-86.521, P = 0.042), East China (OR = 18.049, 95% CI: 2.258-144.259, P = 0.006), Central China (OR = 25.560, 95% CI: 3.210-203.502, P = 0.002), South China (OR = 11.141, 95% CI: 1.395-88.947, P = 0.023), Southwest China (OR = 23.200, 95% CI: 2.524-213.286, P = 0.005) and North China (OR = 14.078, 95% CI: 1.756-112.895, P = 0.013) had a better understanding of the 3I system than those in Northwest China. Healthcare workers with more than 20 years of working experience showed less knowledge of the 3I system than those with less than 5 years of working experience (OR = 0.409, 95% CI: 0.215-0.77, P = 0.006).ConclusionThe current levels of knowledge and application of vital sign zero and the 3I system in the healthcare workers of Chinese tertiary hospitals need to be improved. The concept of vital sign zero should be incorporated into the prevention triage system of infectious diseases.